Market Imperfections and Income Distribution - Yilmaz, Ensar (WALTER DE GRUYTER GMBH, 2016)
This paper aims to search links between market imperfections and functional income distribution. For this purpose we construct a two-sector model - wage goods and luxury goods producing sectors - incorporating imperfections of the product and labor markets under income inequality. In a structure with interdependent and partially monopolistic and competitive markets, we analytically trace up the effects of the changes in power relations proxied by the degree of mark-ups in the product and labor market. The model shows that price and wage mark-ups in two sectors have crucial income distribution implications for the agents in the economy to varying extents. It also demonstrates the effect of the existence of the differentiated consumption patterns arising from income inequality on income distribution. Furthermore, it seems that unemployment level creates externalities on wage rate and on corporate taxes of firms.
Keywords: market power; income distribution; UNEMPLOYMENT; GROWTH; TAXATION; Business & Economics